2019
DOI: 10.1007/s13202-019-0671-4
|View full text |Cite
|
Sign up to set email alerts
|

The effect of alkaline–surfactant on the wettability, relative permeability and oil recovery of carbonate reservoir rock: experimental investigation

Abstract: Due to the increasing demand and the price of hydrocarbon fuels, today, cost-effective enhanced recovery of oil and gas reservoirs has become one of the most interesting research topics. Since the Iranian reservoirs have a considerable potential to apply the chemical EOR processes, it seems that extensive research in this field is inevitable. One of the most important enhanced oil recovery techniques is injecting alkaline-surfactant into the reservoir. Although injecting alkaline-surfactant has been investigat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(5 citation statements)
references
References 17 publications
1
4
0
Order By: Relevance
“…Ultimately, the current case is representing medium oil which makes the generation of bulk oil as expected. A similar observation has been noticed in previous work by Hosseini et al (2019). The recovery factor trend, as seen in Fig.…”
Section: Effect Of Csf On Oil Recovery and Productionsupporting
confidence: 91%
“…Ultimately, the current case is representing medium oil which makes the generation of bulk oil as expected. A similar observation has been noticed in previous work by Hosseini et al (2019). The recovery factor trend, as seen in Fig.…”
Section: Effect Of Csf On Oil Recovery and Productionsupporting
confidence: 91%
“…This observation is consistent with the studies in the literature, indicating cationic surfactants (e.g., CTAB) as being more effective compared to anionic surfactants (e.g., SDS) in changing the wettability toward water wet. 42,43 The water droplets spread immediately on the surface of MNP@CTAB and reach a CA of 0°within 2 s. In addition, the dodecane droplets spread rapidly on the MNP-S@CTAB surfaces and give a CA of 0°. The results verify the hydrophilic and oleophilic properties of MNP-S@CTAB.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Enhanced oil recovery (EOR) techniques are commonly utilized to recover trapped oil in the matrix. These methods include miscible/immiscible gas injections, surfactant, alkali, polymer, and nanoparticles. Low salinity water (LSW) and engineered (smart) water (EW) have gained significant attention among the various EOR techniques due to their ability to alter the wettability of reservoir rocks toward a more water-wet state, thereby improving oil recovery. , Previous studies have also demonstrated that LSW and EW are cost-effective, environmentally friendly, and easy to implement . Combining LSW or EW with chemicals can create an effective hybrid EOR method that enhances oil recovery. …”
Section: Introductionmentioning
confidence: 99%